PEMBELAJARAN MENULIS AKADEMIK BERBANTUAN KECERDASAN BUATAN: PENGARUHNYA TERHADAP KUALITAS ARGUMENTASI DAN KESADARAN METAKOGNITIF MAHASISWA PBSI UNM - Anita Candra Dewi (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study aims to analyze the effect of Artificial Intelligence-assisted academic writing learning on the quality of argumentation and metacognitive awareness of students in the Indonesian Language and Literature Education Study Program at Makassar State University. This study used a quasi-experimental design with a pretest–posttest control group design. The subjects consisted of two classes, each with 37 students. The experimental class received AI-assisted academic writing learning, while the control class received conventional writing learning. Research data were obtained through an academic writing test to measure argumentation quality and a metacognitive awareness questionnaire to determine students' level of cognitive reflection during the writing process. Data were analyzed using descriptive and inferential statistical analysis through t-tests to determine significant differences between the two groups. The results showed that AI-assisted academic writing learning had a significant impact on improving the quality of students' argumentation. In addition, the use of AI also increased students' metacognitive awareness in planning, monitoring, and evaluating their writing process. These findings indicate that the integration of AI in writing learning not only improves the quality of academic writing products but also strengthens students' reflective thinking processes. Thus, the use of AI can be an innovative strategy in academic writing learning in higher education.